A revision of Nearctic species of the genera Adota Casey, 1910 and Psammostiba Yosii & Sawada, 1976 (Coleoptera: Staphylinidae: Aleocharinae) - Gusarov, Vladimir I. (Zootaxa, 2003)
Holarctic genera Psammostiba Yosii & Sawada, 1976 (new to North America) and Adota Casey, 1910 are redescribed. Halostiba Yosii & Sawada, 1976 is placed in synonymy with Adota Casey, 1910. Keys to Nearctic species of Adota and Psammostiba are provided. Adota colpophila Gusarov, sp. n. from Mexico and Psammostiba kenaii Gusarov, sp. n. from Alaska, British Columbia and California are described. Atheta setositarsis Casey, 1910, At. subintima Casey, 1910, At. scortea Casey, 1911, At. scolopacina Casey, 1911 and At. insons Casey, 1911 are placed in synonymy with Adota maritima (Mannerheim, 1843). Three Palaearctic species, Atheta ushio (Sawada, 1971), At. magnipennis Bernhauer, 1943 and At. madida Bernhauer, 1907 are transferred to Adota. Lectotypes are designated for Atheta massettensis Casey, 1910, At. subintima Casey, 1910, At. scortea Casey, 1911, At. scolopacina Casey, 1911 and At. insons Casey, 1911. Atheta finita Moore & Legner, 1975 (replacement name for At. definita Casey, 1911), At. pavidula Casey, 1911 and At. irrita Casey, 1911 described by Casey in Atheta (Adota) do not belong to Adota. Psammostiba Yosii & Sawada, 1976 is raised to generic rank and Adota comparabilis (Mäklin in Mannerheim, 1853) is transferred to Psammostiba